Annotated bird sighting list for spring 1981 compiled by Thomas Staudt - Staudt, Thomas J.et al (1981)
An annotated list of birds sighted by Thomas Staudt. Includes a detailed description of a Ruby-crowned Kinglet sighting and a form documenting the sighting of a Peregrine Falcon at Cou Falls. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1981. Epson - sheet feed